Information System of Office Stationery Inventory PT. Jagad Kreatif Nusantara - Dyah Pitaloka Permata Hadi; Debi Irawan; En Tay; Feri Alpiyasin; Fikri Irawan Abdurahman (LPPM STMIK Mardira Indonesia, 2023)
PT. Jagad Kreatif Nusantara uses the Microsoft Excel program to store inventory for office stationery, such as demand, expenditure, and stock data. That is why there are problems at PT. Jagad Kreatif Nusantara, namely difficulties in finding demand and expenditure data, difficulties in identifying initial stock, preparing reports that should be presented, and then compiling the appropriate information for the needs of inventory of ATK goods.With the development of this Information System application, it is hoped that it can solve these problems. Besides that, the existence of a computerized system in presenting complete information and being able to access data and information quickly in terms of data processing, efficient in terms of personnel, and accurate in terms of information will make work easier.